Monetary Unions of Small Currencies and a Dominating Member: What Policies Work Best for Benefiting from the CMA? - Andreas Wörgötter; Zuzana Brixiova (Institute of Labor Economics (IZA), 2020)
This policy paper underscores the importance of credible currency regimes and their macroeconomic underpinnings for stability in financial systems and long-term economic convergence of developing and emerging market economies. It suggests that for developing regions such as Sub-Saharan Africa, taking steps toward fixed exchange rate frameworks, as a milestone on the path to monetary union, could provide credibility that individual countries struggle to attain on their own. Specifically, fixed arrangements, can restrain unsustainable policies among small economies and enable them to achieve greater stability at lower costs. The paper provides successful examples in this area. Moreover, while it is well-understood that monetary unions and fixed exchange rate regimes among countries with heterogeneous economies are difficult to sustain, the paper notes that heterogeneity can be accommodated in regimes with one dominant member and diverse countries that enhance the flexibility of their labour and product markets and have flexible internal pricing systems. This opens up the question of what might work for African economies, which are heterogeneous and do not meet the optimal currency criteria. The paper examines the convergence performance of small current and past members of the Common Monetary Area (CMA) against the benchmark of South African provinces. The results confirm that a monetary union alone is no guarantee for good outcomes: Among the three small CMA members one (Namibia) is overperforming, one (Eswatini) is average and Lesotho is underperforming. The paper concludes with country-specific and CMA-wide policy recommendations for higher growth of the CMA member countries.
Keywords: F02; F45; O11; 330; asymmetric monetary union; flexibility; regional convergence; Africa